LEARNING BY OBSERVATION MAY ARISE AS A SIGNIFICANT LEARNING STRATEGY FOR STUDENTS WITH DIFFICULTIES IN THE EARLY GRADES OF ELEMENTARY SCHOOL - Valéria Moro Labs, Alva; Escame Gimiliani, Tiago (Revista Gênero e Interdisciplinaridade, 2022)
The article emphasizes that there are many challenges in the educational area that the teacher faces, referring to students with learning difficulties and that observational learning can emerge as a strategy to help in learning. According to Bandura (1969), process knowledge through modeling enables individuals to effect personal, organizational and social changes. It is clear that the number of students who experience difficulties in learning has increased considerably, which leads many of them to lose interest in school, creating a climate of insecurity and loss of self-esteem. School failure affects the subject’s learning in its manifestations without imprisoning intelligence: it often arises from the clash between the learner and the educational institution that works in a segregated way. According to Fernández (1990), learning difficulties are “fractures” in the learning process, where the organism, the body, intelligence and desire are at stake.